Competência para o autocuidado na administração de insulina por septuagenários ou mais idosos - Mayara Sousa Vianna (2016)
The aging population, the increasing prevalence of diabetes in the elderly and increased use of insulin to treat type 2 diabetes demonstrate the need for studies to guide approaches to care for elderly insulinized. What is observed in the elderly routine is that actions involving self-care to control blood sugar, such as self-administration of insulin and blood glucose monitoring, are not always managed properly, making it difficult to control and expose the elderly to greater risks of acute and chronic complications. The practice of self-administration of insulin may suffer interference from several factors, such as cognitive impairment, disability and loss of autonomy and independence, very common in the elderly, that need to be investigated in order to be worked out and minimized the role of health professionals. OBJECTIVE: To assess the competence for self-care insulin administration by septuagenarian or more older with diabetes. METHODOLOGY: This is a cross-sectional study, carried out through home visits, with 148 septuagenarian or more older who acquired insulin in any of the health centers in the Northwest district of Belo Horizonte and conducting the home self-administration of this drug. Collecting sociodemographic and clinical data of elderly and record of changes in the physical, mental and motivational was held. The second time was the observation of insulin self-administration process and registration of errors and hits found. For the assessment of capabilities, we used the Scale for Diabetic Racing identification for self-care, proposed by NUNES (1982). RESULTS: The profile of the elderly was characterized as a predominantly female population (64.2%), from the country side of Minas Gerais (61.5%), with no spouse (54.7%), with less than or equal to 4 years education study (59.5%). The predominant age group was 70 to 79 years (73.6%). In the evaluation of errors in insulin self-administration, the most frequent were the washing of hands (87.2%), the suction air into the syringe and injected into the insulin vial (74.3%) and disposal of sharps in vial hard (73.1%). The results of univariate analysis showed a statistically significant association of competence for satisfactory self-care with: not retired, use of two types of insulin, needle reuse by 2 to 8 times, performing blood glucose, preserved mental state, the correct definition of the site of insulin delivery, correct performance of subcutaneous fold for application insulin and the introduction of the needle for insulin delivery at an angle of 90 °. Considering the multivariate model, responsibility for self-care was negatively associated to the variable to be retired by the INSS and positive association for the variables performs blood glucose and insulin to subcutaneous fold application. It confirmed the competence to poor self-care of the elderly, being satisfactory in only 35.1% of cases. CONCLUSIONS: Knowing the main errors found in insulin self-administration and how they relate to the competence for self-care allows a better programming of the multidisciplinary team to carry out the guidelines for the elderly on care in insulin application. It is hoped that this research will serve as a health service managers benefit in planning intersectoral public policies and building care protocols, specifically tailored for elderly people with diabetes, with special attention to their seventies and older. The maintenance studies related to the competence of the elderly self-care is crucial to deepen the issue and devise strategies to encourage the elderly fitness identification for self-care, and contribute to the full, optimized and assertive health care of this population. It highlights the need for research that contributes to the development of instruments to assess the competence of the elderly for self-administration of insulin in order to ensure self-administration well indicated by health professionals, avoiding the possible complications of the common mistakes in this practice.